Delay and synchronization control middleware to support real-time multimedia services over wireless PCS networks. - Hang Liu (IEEE Journal on selected areas in communications)
This paper presents a discussion of several middleware design issues related to the support of real-time multimedia communications over wireless personal communication services (PCS) networks. Specific interests are given to error recovery and synchronization mechanisms. A hybrid automatic repeat request (ARQ) scheme is employed for error control in the proposed system because it can efficiently adapt to nonstationary wireless channels and yield high throughput and reliability. In particular, delay and delay jitter control related to retransmissions in the error control module are addressed. An adaptive source rate control mechanism is used to handle the fluctuation of the effective channel data rate due to retransmissions. An adaptive synchronization scheme is developed to compensate for long-term delay variation caused by large-scale fading so that synchronization is preserved and end-to-end delay is kept low. Simulation results from the performance evaluation of the system are presented